2023
DOI: 10.1038/s41419-023-05633-2
|View full text |Cite
|
Sign up to set email alerts
|

Dasabuvir suppresses esophageal squamous cell carcinoma growth in vitro and in vivo through targeting ROCK1

Abstract: Esophageal squamous cell carcinoma (ESCC) is an upper gastrointestinal cancer with high morbidity and mortality. New strategies are urgently needed to prolong patients’ survival. Through screening FDA-approved drugs, we found dasabuvir, a drug approved for hepatitis C virus (HCV) treatment, suppressed ESCC proliferation. Dasabuvir could inhibit the growth of ESCC cells in a time and dose-dependent manner and arrested cell cycle at the G0/G1 phase. The antitumor activity was further validated in vivo using pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The application of FDA-approved drugs for cancer treatment has been a hotspot for studying pharmacokinetics, establishing safety in humans, and evaluating toxicity 31 , 32 . Consequently, it may be an intriguing strategy to utilize FDA-approved drugs for ESCC treatment, and several drugs have been demonstrated to have anti-cancer effect in ESCC, such as dasabuvir 48 (for hepatitis C virus treatment), azelnidipine 49 (for hypertension), penfluridol 50 (an antipsychotic drug), and antitussive 51 (an antitussive agent). In this study, we identified an FDA-approved drug, dexrazoxane, as a potential anti-cancer drug for ESCC both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The application of FDA-approved drugs for cancer treatment has been a hotspot for studying pharmacokinetics, establishing safety in humans, and evaluating toxicity 31 , 32 . Consequently, it may be an intriguing strategy to utilize FDA-approved drugs for ESCC treatment, and several drugs have been demonstrated to have anti-cancer effect in ESCC, such as dasabuvir 48 (for hepatitis C virus treatment), azelnidipine 49 (for hypertension), penfluridol 50 (an antipsychotic drug), and antitussive 51 (an antitussive agent). In this study, we identified an FDA-approved drug, dexrazoxane, as a potential anti-cancer drug for ESCC both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of 5-Fu that was used in this study was based on our published article 21 . The dosage of DSV was selected according to a published article and our preliminary experiment 46 . For each animal, three different investigators were involved: two investigators (S.H.…”
Section: Methodsmentioning
confidence: 99%